Beam Formation Studies on the CERN IS03b H Source. Issue 1 (1st April 2022) - Lettry, J; Vnuchenko, A; Bertolo, S; Mastrostefano, C; O'Neil, M; di Lorenzo, F; Coutron, Y; Steyeart, D; Riffaud, B; Thiboud, J; Guida, R; Kapusniak, K; et al.
Abstract: An H - ion source is being operated at the new 160 MeV linear injector (Linac4) of the CERN accelerator complex. The source's plasma is of the Radio Frequency Inductively Coupled Plasma type (RF-ICP), without magnetic cusp and runs with Cs-loss compensation [1]. Vertical downward oriented filter- and electron dump-dipolar magnetic fields expand over the plasma chamber, beam-formation, beam-extraction and electron dump regions and generate horizontal asymmetry and beam angular deflection partially compensated by mechanical alignment of the front-end. The H - beam is generated via volume and caesiated plasma surface modes, the latter inducing a radial asymmetry characterized by an increased current density close to the plasma electrode surface [2]. Asymmetries affecting the meniscus shape, or its current density have to be simulated via 3D Particle In Cell Monte Carlo (PIC-MC) solvers, such as the Orsay Negative Ion eXtraction code (ONIX) [3]. Validation of these simulations require dedicated measurements. This contribution describes experimental methods newly implemented at CERN's ion source test stand and initial results for Optical and Beam Emission Spectroscopy (OES, BES), emittance and beam profile measurements. In a later stage, the gathered data sets can be compared to source plasma parameters and extracted beam parameters from PIC-MC simulations, once coupled to the Ion Beam Simulation (IBSimu) [4] beam transport code. The experimental parameter space includes RF-power, density of neutrals, position of the RF coil and extraction field. Beams of H -, D - and protons were produced; examples of measured data are presented in this contribution.